2015
DOI: 10.1208/s12249-015-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

Topical Delivery of 5-Fluorouracil from Pheroid™ Formulations and the In Vitro Efficacy Against Human Melanoma

Abstract: Abstract. Drug delivery vehicles can influence the topical delivery and the efficacy of an active pharmaceutical ingredient (API). In this study, the influence of Pheroid™ technology, which is a unique colloidal drug delivery system, on the skin permeation and antimelanoma efficacy of 5-fluorouracil were investigated. Lotions containing Pheroid™ with different concentrations of 5-fluorouracil were formulated then used in Franz cell skin diffusion studies and tape stripping. The in vitro efficacy of 5-fluoroura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…For an effective transdermal anticancer activity, chemotherapeutic agents need to exert their action with minimal side effects. This can be achieved if a drug was able to diffuse and accumulate mainly in the epidermis and dermis [54,55]. Therefore, amounts of drugs present in different skin layers were evaluated.…”
Section: Ex Vivo Skin Permeability Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For an effective transdermal anticancer activity, chemotherapeutic agents need to exert their action with minimal side effects. This can be achieved if a drug was able to diffuse and accumulate mainly in the epidermis and dermis [54,55]. Therefore, amounts of drugs present in different skin layers were evaluated.…”
Section: Ex Vivo Skin Permeability Studiesmentioning
confidence: 99%
“…Results also showed that there was significant increase in the penetration of 5-FU through the skin when using MSN-NH 2 in comparison to gel alone ( Figure 9A). It is usually less likely for a hydrophilic drug such as 5-FU to remain in the dermis due to the lipophilic nature of skin [54]. However, MSN-NH 2 seems capable of significantly increasing the accumulation of 5-FU in skin layers to a concentration which was around 10 times higher than control, 149.53 ± 17.4 µg/cm 2 and 12.71 ± 3.3 µg/cm 2 for 5-FU MSN-NH 2 and control, respectively.…”
Section: Ex Vivo Skin Permeability Studiesmentioning
confidence: 99%
“…The influence of drug delivery system on the skin permeation and antimelanoma efficacy of 5‐FU was investigated by Chinembiri et al…”
Section: Resultsmentioning
confidence: 99%
“…The influence of drug delivery system on the skin permeation and antimelanoma efficacy of 5-FU was investigated by Chinembiri et al 38 Published studies have proven the role of novel encapsulated systems like Pheroid™ technology and nanosystems in enhancing skin retention, extended and targeted drug release protection of the drugs, and lower skin irritation. 39 New excipients, refined processing techniques, and a better knowledge of the physicochemical properties of vehicles and drugs have led to the development of new delivery systems.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…5-FU changes into active metabolite such as fluorodeoxyuridine monophosphate (FdUMP), fluorodeoxyuridine triphosphate (FdUTP) and fluorouridine triphosphate (FUTP) [6]. Furthermore, it causes activation of p53 and dysfunction of mitochondria in releasing cytochrome c and then induces the apoptosis pathway [7]. However, this research was designed to evaluate the effectivity of 5-FU cream from National Cancer Center-Dharmais Cancer Hospital product for squamous cell precancerous lesion through Ki67 expression compared with 5% imiquimod cream commercial product.…”
Section: Introductionmentioning
confidence: 99%